Conditional Subgradient Method for Solving Nonsmooth Multi-Objective Optimization Problems - Lahmdani, A.; Tifroute, M. (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, we propose a method for solving quasiconvex nonsmooth multiobjective optimization problems. The proposed method extends the conditional subgradient method, from mono-objective to multiobjective optimization problems. We show that the sequence generated using this method converge to Pareto optimal points of the problem.